2009
DOI: 10.1007/s11055-009-9162-2
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Neuropil Ultrastructure in Hippocampal Field CA1 in Rat Pups after Application of Hyaluronidase

Abstract: Electron microscopy and electrophysiological studies were performed on cross-sectional slices of the hippocampus of four-week-old male rat pups (n = 35) to detect ultrastructural changes in hippocampal field CA1 and the characteristics of the formation of excitatory postsynaptic potentials in this area of the brain after incubation of slices in hyaluronidase solution (10 U/ml), whose specific substrate is the extracellular matrix glycosaminoglycan hyaluronic acid. At 1.5 min after enzyme application, there wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Hyaluronan is a major component of the extracellular matrix in the brain, and contributes to perineuronal net-mediated regulation of neuronal signalling and synaptic plasticity in developmentally mature neurons464748. Herein, we provide new in vitro evidence that cortical neurons express the entire family of HAS enzymes, and produce hyaluronan on multiple structures important for neuronal development and synaptic function.…”
Section: Discussionmentioning
confidence: 95%
“…Hyaluronan is a major component of the extracellular matrix in the brain, and contributes to perineuronal net-mediated regulation of neuronal signalling and synaptic plasticity in developmentally mature neurons464748. Herein, we provide new in vitro evidence that cortical neurons express the entire family of HAS enzymes, and produce hyaluronan on multiple structures important for neuronal development and synaptic function.…”
Section: Discussionmentioning
confidence: 95%
“…However, a number of studies have suggested that HA within perineuronal nets can influence neuron activity that can be altered by hyaluronidase treatment. For example, the removal of perineuronal nets using hyaluronidase in hippocampal slices from young rats reduced the width of the synaptic cleft and increased the amplitude of excitatory postsynaptic potentials in CA1 axodendritic connections [ 56 ]. From this and other studies, it is reasonable to conclude that HA-rich perineuronal nets could influence both the efficacy and architecture of synapses.…”
Section: Endogenous Hyaluronidases Influence Cns Repairmentioning
confidence: 99%
“…In another study, hippocampal slices from young rats were treated with hyaluronidase to remove PNNs (120). Scanning electron microscopy (SEM) and ex vivo electrophysiological recordings showed that hyaluronidase treatment dramatically reduced the width of the synaptic cleft and increased the amplitude of excitatory postsynaptic potentials in CA1 axodendritic connections.…”
Section: Ha and The Developing And Adult Cnsmentioning
confidence: 99%